Mental Health Literacy Levels of Medical Staff in China: An Assessment Based on a Meta-Analysis - Guo, Shengyu; Xiong, Jie; Liu, Feiyue; Su, Yanlin (Frontiers in Psychiatry, 2021)
Background: The awareness rate of mental health knowledge among medical staff is an important evaluation index to assess the service capacity of a country or region, and this indicator in China has not been quantitatively evaluated. Study Design: This study systematically combined pertinent quantitative study data from previous related studies to conclude the awareness rate of mental health knowledge among Chinese medical staff. Methods: Related studies from five electronic databases were searched, and a meta-analysis was conducted to obtain the combined result. The primary outcome of the present study was the awareness rate of medical staff or the sample size and the number of those who can answer the relevant questions correctly. We also performed a hierarchical analysis according to the sample group's region and specialty. The awareness rate of medical staff and corresponding 95% confidence intervals (CIs) were calculated. The heterogeneity was assessed with the I2 test, and Egger's test was used to evaluate publication bias. Results: A total of 15 articles with 11,526 medical staff were included in the present study; the overall awareness rate of mental health knowledge among Chinese medical staff was as low as 81%. The awareness rate of mental health knowledge among medical workers in developed regions is higher than that in developing regions. The awareness rate of mental health among medical staff in the department of psychiatry, non-psychiatry, and community medical staff was 88, 68, and 82%, respectively. Conclusion: The overall awareness rate among medical staff in this country is unsatisfactory, and the awareness rate in developed regions is higher than medical staff in developing regions. Psychiatric hospital staff has a higher awareness rate than community medical staff, and non-psychiatric hospital staff has the lowest awareness rate.